Estimation of lung shunt fraction from simultaneous fluoroscopic and nuclear images. (11th October 2017) - van der Velden, Sandra; Bastiaannet, Remco; Braat, Arthur J A T; Lam, Marnix G E H; Viergever, Max A; de Jong, Hugo W A M
Abstract: Radioembolisation with yttrium-90 ( 90 Y) is increasingly used as a treatment of unresectable liver malignancies. For safety, a scout dose of technetium-99m macroaggregated albumin ( 99m Tc-MAA) is used prior to the delivery of the therapeutic activity to mimic the deposition of 90 Y. One-day procedures are currently limited by the lack of nuclear images in the intervention room. To cope with this limitation, an interventional simultaneous fluoroscopic and nuclear imaging device is currently being developed. The purpose of this simulation study was to evaluate the accuracy of estimating the lung shunt fraction (LSF) of the scout dose in the intervention room with this device and compare it against current clinical methods. Methods: A male and female XCAT phantom, both with two respiratory profiles, were used to simulate various LSFs resulting from a scout dose of 150 MBq 99m Tc-MAA. Hybrid images were Monte Carlo simulated for breath-hold (5 s) and dynamic breathing (10 frames of 0.5 s) acquisitions. Nuclear images were corrected for attenuation with the fluoroscopic image and for organ overlap effects using a pre-treatment CT-scan. For comparison purposes, planar scintigraphy and mobile gamma camera images (both 300 s acquisition time) were simulated. Estimated LSFs were evaluated for all methods and compared to the phantom ground truth. Results: In the clinically relevant range of 10–20% LSF, hybrid imaging overestimated LSF with approximately 2 percentage points (pp) and 3 pp for the normal and irregular breathing phantoms, respectively. After organ overlap correction, LSF was estimated with a more constant error. Errors in planar scintigraphy and mobile gamma camera imaging were more dependent on LSF, body shape and breathing profile. Conclusion: LSF can be estimated with a constant minor error with a hybrid imaging device. Estimated LSF is highly dependent on true LSF, body shape and breathing pattern when estimated with current clinical methods. The hybrid imaging device is capable of accurately estimating LSF within a few seconds in an interventional setting.